2019
DOI: 10.12691/jfnr-7-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Feeding Practices and Its Association with Early Childhood Caries

Abstract: Early childhood caries (ECC) is one of the most prevalent dental diseases among children and is related to their early feeding practices. This multi-factorial disease involves susceptible tooth and host, fermentable carbohydrates in the diet, cariogenic micro-organisms and time (American Academy of Pediatric Dentistry, 2008). Thus, this study aimed to identify the associations between bottle-feeding and weaning practices, and ECC formation. By using convenience sampling, 201 children were recruited from the II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This report also found higher frequency of putting child to sleep using bottle (97.9%) than previous local study (25) However, in this study, oral pain was the most commonly reported impact at 26.2%. This reflected the situation in which the state of Kelantan had the highest prevalence of ECC at 88.7% (2), although the occurrence of dental caries in young children do not necessarily involve pain, in particular, the incipient stage.…”
Section: Discussionsupporting
confidence: 48%
“…This report also found higher frequency of putting child to sleep using bottle (97.9%) than previous local study (25) However, in this study, oral pain was the most commonly reported impact at 26.2%. This reflected the situation in which the state of Kelantan had the highest prevalence of ECC at 88.7% (2), although the occurrence of dental caries in young children do not necessarily involve pain, in particular, the incipient stage.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, Kim et al ( 87 ) recorded in their study conducted in the United States, that among the studied subjects, 26% of young adults lost one or more teeth in association with massive intake of sweetened juices. Interestingly, frequent and prolonged bottle-feeding practices, as well as high consumption of sweet drinks during weaning, could be associated with the formation of early childhood caries ( 88 ). It is important to increase the awareness among parents concerning bottle-feeding practices and weaning diet contents and highlight the potential implication for their children's oral health.…”
Section: Discussionmentioning
confidence: 99%
“…22 Rusali et al reported the prevalence of ECC to be significantly (p <0.001) high among children who were bottle-fed for more than four years. 23 Similarly, in Jeddah (Saudi Arabia) it was observed that children who bottlefed in bed had a 9% greater risk of caries compared to children who did not. 19 Another study from south-west Germany reported a significant correlation between the usage of nursing bottles in bed and severe ECC.…”
Section: Discussionmentioning
confidence: 97%